O13 Iris advise: assessing for domestic violence in sexual health environments (a pilot study). (18th May 2015) - Pathak, Neha; Sohal, Alex; Berry, Judith; Apea, Vanessa; Blake, Sarah; Bailey, Jayne; Feder, Gene
Abstract : Background/introduction: Sexual health and gynaecological problems are the most consistent and largest physical health differences between abused and non-abused populations. Sexual health services are well placed to identify and support people experiencing domestic violence and abuse (DVA). Most sexual health professionals have no DVA training despite NICE recommendations. IRIS (Identification and Referral to Improve Safety) is a national GP training intervention that improved the primary-care response to DVA. Aim(s)/objectives: To pilot an IRIS-based training intervention on assessing for domestic violence in sexual health environments (ADViSE), and evaluate its feasibility and effectiveness. Methods: ADViSE was developed and implemented in two sexual health clinics (Site 1 and 2) using a mixed methods design: quantitative analysis of electronic patient records and qualitative analysis of staff interviews, written feedback and anonymised cases. The intervention comprised electronic prompts, multidisciplinary training sessions, clinic materials, and specialised referral pathways to advocate-educators (AE). The pilot lasted 7 weeks at Site 1 and is ongoing at Site 2 to last 12 weeks. Results: Site 1 achieved a 10% enquiry rate (N = 267), 6% disclosure rate (n = 16) and 8 AE referrals. At 8 weeks, Site 2 has achieved a 60% enquiry rate (N = 2113), a 4.5% disclosure rate (n = 90) and 9 AE referrals. Staff reported increased confidence in identifying and managing DVA. No DVA cases were recorded in the 3 months preceding the pilots. Conclusion/recommendations: IRIS ADVISE can be successfully developed and implemented in sexual health clinics, fulfilling an unmet need for DVA training. Further evaluation through a larger multicentre study is now necessary.